Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 11 - Biting activity and blood-seeking parity of Anopheles (Kerteszia) in South-Eastern Brazil - Oswaldo Paulo Forattini; Iná Kakitani; Eduardo Massad; Daniel Marucci
An. (Ker.) cruzii and An. (Ker.) bellator were monitored by the use of human bait and Shannon trap collections during a one-year period in 1994. Indoor and outdoor collections were made on human bait and inside the forest environment a Shannon trap was used. Both were undertaken in the evening crepuscular period. Results showed a greater abundance of An. cruzii in the forest, where as An. bellator was more abundant in the domiciliary environment. Through the application of the Polovodova method an age grading was established. Computing the parous and nulliparous females with Christopher's Stage III and above, more than 30.0% of blood-seeking specimens of both anophelines had had a previous blood meal. The higher abundance of An. bellator as compared with that of An. cruzii in the domiciliary environment may be explained by the influence of the neighboring low-lying coastal islands of the estuary system.